Themis: An Efficient and Memory-Safe BFT Framework in Rust (Research Statement) - Schwarz-Rüsch, Signe; Bleeke, Kai; Kapitza, Rüdiger (3rd Workshop on Scalable and Resilient Infrastructures for Distributed Ledgers (SERIAL 2019), 2019)
Byzantine fault tolerant (BFT) protocols have previously been developed mainly in C or Java. C offers high performance but is more error-prone, leading to more potential Byzantine faults, whereas Java offers memory safety at the cost of performance. The Rust programming language combines the performance advantages of C with safe memory management, and newer releases now enable the implementation of complex, non-blocking asynchronous frameworks, as is needed for efficient BFT frameworks. We present a BFT framework implementation in Rust and preliminary performance evaluations for the PBFT protocol.<br
Keywords: Rust; blockchain; Byzantine fault tolerance